2016
DOI: 10.1007/s00429-016-1199-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Kir4.1 and Kir5.1 inwardly rectifying potassium channels in oligodendrocytes, the myelinating cells of the CNS

Abstract: The inwardly rectifying K+ channel subtype Kir5.1 is only functional as a heteromeric channel with Kir4.1. In the CNS, Kir4.1 is localised to astrocytes and is the molecular basis of their strongly negative membrane potential. Oligodendrocytes are the specialised myelinating glia of the CNS and their resting membrane potential provides the driving force for ion and water transport that is essential for myelination. However, little is known about the ion channel profile of mature myelinating oligodendrocytes. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
72
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 71 publications
4
72
1
Order By: Relevance
“…This is an intriguing result given that Kir5.1‐containing Kir channels have not been implicated in hypoxia‐sensing mechanisms within the glomus cells of the carotid bodies or the recently proposed astrocyte‐mediated hypoxia‐sensing mechanisms in the brain (3133). However, Kir5.1 expression has been detected in the carotid bodies (34) and brainstem astrocytes and glia (6,9), and both have known pH sensitivity (10, 35). Despite the loss of the hypoxic ventilatory response in SS Kcnj16−/− rats, it is possible that the chronic metabolic acidosis leads to hyperventilation at rest through a carotid body‐mediated mechanism given that the blood–brain barrier protects the brain to a large extent during systemic metabolic acidosis (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an intriguing result given that Kir5.1‐containing Kir channels have not been implicated in hypoxia‐sensing mechanisms within the glomus cells of the carotid bodies or the recently proposed astrocyte‐mediated hypoxia‐sensing mechanisms in the brain (3133). However, Kir5.1 expression has been detected in the carotid bodies (34) and brainstem astrocytes and glia (6,9), and both have known pH sensitivity (10, 35). Despite the loss of the hypoxic ventilatory response in SS Kcnj16−/− rats, it is possible that the chronic metabolic acidosis leads to hyperventilation at rest through a carotid body‐mediated mechanism given that the blood–brain barrier protects the brain to a large extent during systemic metabolic acidosis (36).…”
Section: Discussionmentioning
confidence: 99%
“…Among other genes we identified was Kcnj16 , which encodes the inwardly rectifying K + (Kir) 5.1 channel. The Kir5.1 subunit is thought to primarily form heterotetrameric channels with other Kir family members, particularly with Kir4.1 and Kir2.1 channels (9,10). Atypically, they may function independently as a homomeric Kir5.1 channel (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are 92 human genes encoding different potassium channels [HUGO Gene Nomenclature Committee (HGNC) Database, www.genenames.org]. Some of these channels such as KCNJ10 and KCNJ16 are restricted to oligodendrocytes where they maintain the resting potential of oligodendrocytes necessary for myelin integrity (Brasko et al 2016). Given the neurophysiological roles of potassium channels, genetic variance in potassium channel genes may have a shared common effect on the function of myelinated axons and processing speed.…”
mentioning
confidence: 99%
“…NG2‐glia and oligodendrocytes constitute two major populations of macroglia in the CNS and they are fundamental to neurons' myelin production and formation . A recent study clearly showed K + channel mRNA and protein functional expression in both cell types . It thus becomes necessary and relevant to elucidate a potential interaction of K + channels with myelin‐related genes.…”
Section: Discussionmentioning
confidence: 99%